Metabolic processes control carbon dioxide dynamics in a boreal forest ditch affected by clear-cut forestry - Zannella, Alberto; Eklöf, Karin; Lannergård, Emma; Laudon, Hjalmar; Maher Hasselquist, Eliza; Wallin, Marcus B. (Frontiers in Water, 2023)
Boreal watercourses are large emitters of carbon dioxide (CO2) to the atmosphere. For forestry intensive areas of the Nordic and Baltic countries, a high share of these watercourses are manmade ditches, created to improve drainage and increase forest productivity. Previous studies have suggested that terrestrial sources sustain the CO2 in these ditches and variability in hydrology is the main temporal control. However, few studies have explored ditch CO2 dynamics and its associated controls in catchments being exposed to forest harvest. An altered hydrology, increased nutrient export and light availability following forest harvest are all factors that potentially can change both levels, dynamics, and source controls of ditch CO2. Here, highfrequency (30 min) CO2 concentration dynamics together with other hydrochemical variables were studied in a forest ditch draining a fully harvested catchment in the Trollberget Experimental Area, northern Sweden. We collected data during the snow-free season from May to October. Ditch CO2 concentrations displayed a clear seasonal pattern with higher CO2 concentrations during summer than in spring and autumn. Concentrations ranged from 1.8 to 3.5 mg C L -1 (median: 2.4 mg C L -1 , IQR = 0.5 mg C L -1 ). Strong diel cycles in CO2 developed during early summer, with daily amplitudes in CO2 reaching up to 1.1 mg C L -1 . These pronounced daily cycles in CO2 were closely related to the daily sum of shortwave radiation and water temperature. Variations in hydrology had generally a low impact on the CO2 dynamics but did vary among seasons and between individual hydrological events. It was evident from our study that growing season CO2 concentrations in a forest ditch affected by clear-cut harvest were highly variable and mainly controlled by light and temperature induced metabolism. These high dynamics and the associated controls need to be considered when scaling up ditch CO2 emissions across boreal landscapes affected by intensive forestry.